Elevation affects the ecological stoichiometry of Qinghai spruce in the Qilian Mountains of northwest China - Qin, Huijun; Jiao, Liang; Zhou, Yi; Wu, Jingjing; Che, Xichen (Frontiers in Plant Science, 2022)
Environmental heterogeneity in temperature, moisture, and soil fertility caused by altitude gradients can affect the trade-offs in survival strategies for trees. There is uncertainty about the allocation of resources of different tissues of trees to the altitude gradient based on the responses of carbon (C), nitrogen (N) and phosphorus (P). Here, the C, N and P contents of leaves, branches, trunks, thick and fine roots of Qinghai spruce and their stoichiometric changes in response to different altitudes were investigated in Qilian Mountains. We found that (1) N:P of Qinghai spruce was less than 14 in all tissues at most altitudes, indicating that Qinghai spruce was more susceptible to N limitation. Meanwhile, the N content and N:P of Qinghai spruce were significantly negatively correlated with temperature (p < 0.05), and the P content of Qinghai spruce was lower at high altitude. (2) The contributions of soil and climate interactions to each tissue were 34.02% (leaves), 16.84% (branches), 67.78% (trunks), 34.74% (thick roots), and 49.84% (fine roots), indicating that climate and soil interactions were the dominant factors of C, N, P, and stoichiometry variation in each tissue of Qinghai spruce. The results of the study clarify that the altitude gradient regulates the element contents and resource allocation in Qinghai spruce, providing basic data and important references for future forest management in the regions. These findings also help to improve our understanding of altitudinal patterns of forest ecosystems stoichiometry in the arid and semiarid.